Hand Hygiene Evaluation Using Two Different Evaluation Tools and Hand Contamination of Veterinary Healthcare Workers in a Swiss Companion Animal Clinic - Kira Schmitt (MDPI AG, 2021)
Hand hygiene (HH) is the most important measure to prevent nosocomial infections. HH compliance in companion animal clinics has been reported to be poor. The present study compared an online application with the WHO evaluation form to assess the WHO five moments of HH in a Swiss companion animal clinic. In 202 hand swabs from 87 staff members, total viable count (TVC) before and after patient contact was evaluated and the swabs were tested for selected antimicrobial resistant microorganisms of public health importance. HH compliance (95% confidence interval) was 36.6% (33.8–39.5%) and was similar when assessed with the two evaluation tools. HH differed between hospital areas (p = 0.0035) and HH indications (p < 0.0001). Gloves were worn in 22.0% (18.0–26.6%) of HH observations and were indicated in 37.2% (27.3–48.3%) of these observations. Mean TVC before patient contact was lower (0.52 log CFU/cm2) than after patient contact (1.02 log CFU/cm2) but was similar before patient contact on gloved and ungloved hands. Three hand swabs (1.5% (0.4–4.3%)) were positive for methicillin-resistant Staphylococcus aureus. Gloving should not be regarded as a substitute for HH. Overall, HH in companion animal medicine should urgently be fostered.